SRG/eROSITA 3D mapping of the interstellar medium using X-ray absorption spectroscopy - Gatuzz, E.; Wilms, Jörn; Zainab, Aafia; Freund, S.; Schneider, P. C.; Robrade, J.; Czesla, S.; García, J. A.; Kallman, T. R. (Astronomy & Astrophysics, 2024)
We present a detailed study of the hydrogen density distribution in the local interstellar medium (ISM) using the X-ray absorption technique. Hydrogen column densities were precisely measured by fitting X-ray spectra from coronal sources observed during the initial eROSITA all-sky survey (eRASS1). Accurate distance measurements were obtained through cross-matching Galactic sources with the third Gaia data release (DR3). Despite the absence of a discernible correlation between column densities and distances or Galactic longitude, a robust correlation with Galactic latitude was identified. This suggests a decrease in ISM material density in the vertical direction away from the Galactic plane. We have also investigated the relation between the optical extinction and the hydrogen column density. To do so, we employed multiple density laws to fit the measured column densities, revealing constraints on height scale values (9 < hz < 14 pc). Unfortunately, radial scales and the central density remain unconstrained due to the scarcity of sources near the Galactic center. Subsequently, a 3D density map of the ISM was computed using a Gaussian process approach, inferring hydrogen density distribution from hydrogen column densities. The results unveil the presence of multiple beams and clouds of various sizes, indicative of small-scale structures. High-density regions were identified at approximately 100 pc, consistent with findings in dust-reddening studies, and are potentially associated with the Galactic Perseus arm or the local bubble. Moreover, high-density regions were pinpointed in proximity to the Orion, Chameleon, and Coalsack molecular complex, enriching our understanding of the intricate structure of the local ISM.
CRIS-Team Scopus Importer:2024-09-06
Keywords: ISM: atoms; ISM: structure; Local insterstellar matter; X-rays: ISM